Users' participation in facebook brand pages and its influence on word-of-mouth: the role of brand knowledge and brand relationship - Langaro, D. (2020)
Due to the development of social media, brands have integrated Social Networking Sites (SNS) as an important part of their communication mix. This change calls for studies that help to understand the role of SNS in the communication mix, through further investigating their effects for brands and acknowledging their influencing triggers. Concerning that, previous studies have associated the use of SNS to effects on WoM, with SNS contributing as a tool skilled for generating conversations about the brand. The current study focuses on investigating the triggers of these effects. In previous research, WoM was accepted as being triggered by constructs related to the effects of SNS on increasing users´ knowledge about the brand and improving perceived relationship value. Despite their relevance, studies in SNS so far have not yet explored these approaches in an integrative manner. So researchers and managers could understand how these dimensions behave in relation to each other in triggering WoM. The current study addresses this research gap, proposing an integrative perspective that combines brand knowledge and brand relationship constructs while investigating the effects on WoM. Direct and indirect effects are proposed with mediating relations being supported by the Theory of Reason Action (TRA) and Social Exchange (SET). Two surveys were implemented, with 218 and 550 valid responses obtained. Results were analyzed using structural equation modeling. Findings support the relevance of brand relationship variables (trust and affective commitment) in influencing WoM, with trust assuming a pivotal role. Moreover, triggers related to brand knowledge also influence the effects, with brand awareness and attitude driving significant effects. Managerial and theoretical implications are discussed